PENERAPAN MODEL PEMBELAJARAN SUSAN LOUCKS-HORSLEY UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI PENCEMARAN LINGKUNGAN DI KELAS VII SMPN 40 PEKANBARU - Islami, Assyifa Ahya; Zulhelmi, Zulhelmi; Sahal, Muhammad; Sandra, Meria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to improve the cognitive learning outcomes of students with the implementation of Susan Loucks-Horsley's learning model in the environmental pollution material in class VII of SMPN 40 Pekanbaru. The population in this study was 201 grade VII students of SMPN 40 Pekanbaru. The sample was taken by simple random sampling so that a sample of 80 grade VII students was obtained which consisted of 40 students in the experimental class and 40 students in the control class. The type of this research is included in pre-experimental design. The design used is Intact Group Comparison. The instrument of this study is in the form of multiple choice written cognitive learning outcomes. Data was collected by giving posttest to the study sample. Data analysis in this study used descriptive analysis and inferential analysis. The results of the study showed that in the experimental class the average absorption capacity of students reached 72.125% with a good category and a control class of 66.625% with a fairly good category. From the average absorptive score obtained, the effectiveness of learning in the experimental class and the control class is in a different category, which is effective and quite effective. Based on the results of inferential analysis, there are significant differences in the cognitive learning outcomes of students between classes applying the Susan Loucks-Horsley model and the class applying conventional learning to environmental pollution material. Thus, the Susan Loucks-Horsley learning model can improve the science learning outcomes of science in grade VII SMP 40 Pekanbaru.Key Words: Susan Loucks-Horsley Learning Model, Cognitive Learning Results, Middle School Science Learning, Environmental Pollution